NONPHYSICAL VIOLENCE IN KUNG FU FILM: “黄飞鸿之英雄有梦” - Adhimas, Yogi Bagus; Fitriana, Ephrilia Noor; Chaoqun, Li; Purwaningtyas, Yohanna Aprillia (Universitas Padjadjaran, 2023)
Chinese Kungfu films, which are famous for their physical violence, can also be seen from their non-physical violence. It will not be possible for a fight to be fought without verbal contact between the previous conflicts. This will be an additional perspective that Kungfu films can not only be enjoyed in terms of physical violence but also non-physical violence. Analysis of the film “黄飞鸿之英雄有梦” which uses a descriptive qualitative approach combined with interdisciplinary studies of cognitive linguistic and cultural studies yielded fifteen data that have proven that non-physical violence in Kungfu films has its own beauty. Negative diction, the selection of linguistic components, to the use of idioms as a characteristic of Chinese culture are some of the non-physical violent of the media found. In the end, theoretically and practically this research can be used in many opportunities such as linguistic learning, cultural introduction, or become the basis of future research.